TIPOLOGI DAN MAKNA TINGGALAN MEGALITIK DI PESISIR PANTAI UTARA KABUPATEN JAYAPURA - Erlin Novita Idje Djami (AMERTA, 2017)
Abstract. Typology and Meaning of Megalithic Remains in the North Coast of Jayapura Regency. Megalithic remains are a form of manifestation of social and cultural events in the past. The existence of megalithic findings was encountered in the northern coast of Jayapura regency. Judging from their forms, they are quite diverse and served as a symbol that explains the basis of life of the people of Papua. In respect of this, it is important to reveal the forms, functions, and meanings of the megalithic remains contained in them. The aim of this research is to determine the forms, functions, and meanings of the megalithic remains that represent nation’s identity. Data were collected through literatures, observation of megalithic objects, and interviews with informants. The result of the study on stone seats, menhirs and menhir statues, stone jars, Tajaho Rock, Ancestor Rock, Yendaepiwai Rock, Batu Permen (candy stone), Batu Sukun (breadfruit stone), Batu Lingkar (stone enclosure), Haby pain stove, and Somda Rock, as well as the folklores about those cultural objects reveal that the remains were functioned as seats, media of ceremonies, proof of ownership of indigenous territories, marks of historical origin, place for public discussion, a place that tells a story, a symbol of the ancestors, and historical evidence. The diversity of the megalithic findings is a symbol of their human supporters, which contains the meaning of life as the nation’s cultural character. Keywords: Megalithic remains, Form, Function, Meaning, Northern coastal regency of Jayapura Abstrak. Tinggalan megalitik merupakan suatu bentuk manifestasi dari peristiwa sosial budaya masyarakat masa lampau. Keberadaan temuan megalitik banyak ditemui di pesisir pantai utara Kabupaten Jayapura. Jika dilihat dari bentuknya, temuan itu cukup beragam dan merupakan simbol yang menjelaskan dasar kehidupan orang Papua. Sehubungan dengan itu, menjadi penting untuk mengungkapkan bentuk tinggalan megalitik tersebut, baik fungsi maupun makna yang terkandung didalamnya. Tujuan penelitian untuk mengetahui bentuk, fungsi, dan makna tinggalan megalitik yang menggambarkan jati diri bangsa. Metode pengumpulan data dilakukan melalui studi pustaka, observasi objek megalitik, dan wawancara. Hasil penelitian bentuk tinggalan megalitik berupa kursi batu, menhir, dan arca menhir, Batu Tempayan, Batu Tajaho, Batu Nenek Moyang, Batu Yendaepiwai, Batu Permen, Batu Sukun, Batu Lingkar, Tungku Api (haby pain), dan Batu Somda, serta cerita rakyat yang melingkupi objek budaya tersebut. Tinggalan tersebut berfungsi sebagai tempat duduk, media upacara, bukti kepemilikan wilayah adat, tanda asal sejarah, tempat musyawarah, tempat yang bercerita, simbol nenek moyang, dan bukti sejarah. Keragaman temuan megalitik tersebut merupakan simbol manusia pendukungnya, yang mengandung makna kehidupan sebagai karakter budaya bangsa. Kata Kunci: Tinggalan megalitik, Bentuk, Fungsi, Makna, Pesisir utara Kabupaten Jayapura